Proton ceramic battery air electrode material with low thermal expansion behavior
By mixing the combination of perovskite materials with negative thermal expansion materials in proportion, the heat treatment of low -thermal expansion behaviors has been prepared, and the air electrode material of the battery battery battery with low heating expansion has solved the problem of slow response dynamics at low temperatures at low temperature at low temperature, and improved the operation of the battery operation. Stability and electrochemical performance.
Patent Information
- Application Number
- CN202411397114.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-28
AI Technical Summary
The oxygen reduction reaction and oxygen precipitation reaction of air electrodes of proton ceramic fuel cell (PCC) slow at low temperatures, which affects the performance output and operating stability of PCC.
By mixing the combined combination of SRFEO3-Δ and negative thermal expansion materials (ZRW2O8) for heat treatment by a certain proportion to prepare a proton ceramic battery air electrode material with low thermal expansion behavior.
Effectively reduce the thermal expansion coefficient of the PCC composite air electrode material, improve the thermal mechanical matching between the air electrode and the electrolyte, improve the structural stability and electrochemical properties of the air electrode material, and improve the operating stability of PCC.
Smart Images

Figure CN119381464A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid oxide fuel cells and relates to a proton ceramic battery air electrode material with low thermal expansion behavior. Background Art
[0002] Solid oxide cell (SOC) has two functions: solid oxide electrolyzer (SOEC) and solid oxide fuel cell (SOFC). It is a clean energy conversion and storage device; it can switch between electrolysis and fuel cell modes to achieve efficient conversion of electrical energy and chemical energy. The dual-mode characteristics of SOC make it a promising technology to improve the flexibility, stability and sustainability of energy systems, and it is currently a research focus in the energy field. According to the type of ion transport in the electrolyte, SOC can be divided into oxygen ion conductor SOC (O-SOC) and proton ceramic cell (PCC). Because proton transport has a lower activation energy than oxygen ion transport, PCC is more suitable for operation at medium and low temperatures (450~650 °C) than O-SOC to improve the durability of each battery component. PCC can synthesize hydrogen using excess electricity from renewable energy sources such as wind and solar energy in the proton ceramic electrolyzer (PCEC) mode, and convert the stored hydrogen into electrical energy in the proton ceramic fuel cell (PCFC) mode. However, the sluggish kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at air electrodes at low temperatures affect the performance output and operational stability of PCC, further limiting its practical application.
[0003] Among iron-based perovskite materials, SrFeO 3-δ (SF) has the advantages of high conductivity, catalytic activity and low cost. Therefore, SF air electrode materials have high commercial value. However, due to the high thermal expansion behavior of SF, it does not match other PCC components, which in turn affects the stability of the electrochemical performance of SF-based materials when used as PCC air electrodes. Therefore, researchers need to develop composite materials based on SF materials and improve the technical process of electrode material preparation to develop SF electrode materials with matching thermal expansion behavior and excellent performance. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a proton ceramic battery air electrode material with low thermal expansion behavior, which can effectively reduce the thermal expansion coefficient of the proton ceramic battery composite air electrode material, thereby improving the thermomechanical matching between the air electrode and the electrolyte.
[0005] In order to achieve the above technical purpose, the present invention provides a proton ceramic battery air electrode material with low thermal expansion behavior, which is prepared by mixing a perovskite material and a negative thermal expansion material in a mass ratio of 5 to 10:1 and heat treating. The molecular formula of the perovskite material is SrFeO 3-δ , where δ is the oxygen vacancy content; The molecular formula of the negative thermal expansion material is ZrW2O8.
[0006] Optimally, the mixing is carried out using a high-energy ball mill with a rotation speed of 300-500 rpm and a ball milling time of 0.5-1.5 h.
[0007] Furthermore, the heat treatment temperature is 800-1000°C and the insulation time is 3-5h.
[0008] Optimally, the perovskite material is prepared according to the following steps: Weigh a metal salt and deionized water, mix them, heat and stir until the metal salt is completely dissolved; then add ethylenediaminetetraacetic acid and citric acid, mix and stir, and adjust the pH to 7 to 8; the metal salt is a mixture of Sr(NO3)3 and Fe(NO3)3·9H2O; The water is evaporated under heating conditions to obtain a gel-like substance, which is then dried to obtain a perovskite material precursor; The perovskite material precursor is placed in a muffle furnace for high-temperature heat treatment to obtain the perovskite material.
[0009] Furthermore, the molar ratio of total metal ions, oxalic acid tetraacetic acid and citric acid in the metal salt is 1:0.9~1.1:1.8~2.2, preferably 1:1:2.
[0010] Furthermore, ammonia water or ammonium bicarbonate solution with a mass fraction of 20-30% is used to adjust the pH.
[0011] Furthermore, the drying process is carried out at a temperature of 170-200°C and for a time of 6-8 hours.
[0012] Furthermore, the temperature of the high temperature heat treatment is 900-1100°C and the holding time is 5-8h. The proton ceramic battery air electrode material with low thermal expansion behavior of the present invention is obtained by mixing a perovskite material and a negative thermal expansion material in proportion and performing heat treatment. The negative thermal expansion material is introduced into the air electrode, which can effectively reduce the thermal expansion coefficient of the PCC composite air electrode material, thereby improving the thermomechanical matching between the air electrode and the electrolyte; in addition, the introduction of the negative thermal expansion material can improve the stability of the air electrode material structure and the electrochemical properties, thereby improving the operating stability of the PCC. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 XRD refinement diagram of air electrode materials: (a) air electrode material SF+10 wt% ZW (a) XRD refinement pattern of SFZW; (b) XRD refinement pattern of comparison material SF.
[0014] Figure 2 It is the high temperature XRD pattern of SFZW powder between room temperature and 750°C.
[0015] Figure 3 (a) is the XRD pattern of SFZW powder and BZCYYb powder mixed and calcined at 800°C for 2h. Figure 3 (b) XRD patterns of SFZW material before and after water treatment at 550°C for 150 h.
[0016] Figure 4 The air electrode material is the thermal expansion curve of the SF and SFZW samples in Example 1 of the present invention from room temperature to 800°C in air.
[0017] Figure 5 (a) is the Arrhenius plot of the area specific impedance of SF and SFZW symmetric cells. Figure 5 (b) is the impedance curve of SFZW at 500°C, 600°C and 650°C.
[0018] Figure 6 (a) is the electrode impedance of SF and SFZW symmetric cells tested in humid air at 550°C for 300 h. Figure 6 (b) is the comparison of impedance curves of SF and SFZW before and after the stability test.
[0019] Figure 7 It is the SEM image of the cross section of the symmetrical battery prepared by SF and SFZW after 300 h of long-term stability.
[0020] Figure 8 (a) Impedance plots of symmetric battery electrodes prepared with SF and SFZW during 35 cumulative thermal cycles between 600°C and 300°C. (b) Impedance spectra of SFZW during thermal cycling stability test.
[0021] Fig. 9 (a) IV and IP curves of Ni-BZCYYb|BZCYYb|SFZW single cell in fuel cell mode under H2 / air. (b) IV curves of fuel cell and electrolysis mode under H2 / humid air (5% H2O).
[0022] Fig.10 (a) is a single cell containing SFZW at 550°C and a current density of 200 mA cm -2 The battery stability after running for 250 h. Fig.10(b) is a single cell containing SFZW at 550°C and a current density of 600 mA cm -2 The electrolysis stability after 400 h of operation. DETAILED DESCRIPTION
[0023] The proton ceramic battery air electrode material with low thermal expansion behavior of the present invention is prepared by mixing a perovskite material and a negative thermal expansion material in a mass ratio of 5 to 10:1 and heat treating the mixture. The molecular formula of the perovskite material is SrFeO 3-δ , where δ is the oxygen vacancy content (0≤δ≤1); the molecular formula of the negative thermal expansion material is ZrW2O8. The negative thermal expansion material is introduced into the air electrode by mixing the perovskite material and the negative thermal expansion material in proportion and heat treating them, which can effectively reduce the thermal expansion coefficient of the PCC composite air electrode material, thereby improving the thermomechanical matching between the air electrode and the electrolyte; in addition, the introduction of the negative thermal expansion material can improve the stability of the air electrode material structure and the electrochemical performance, thereby improving the operating stability of the PCC.
[0024] The mixing is carried out in a high-energy ball mill with a rotation speed of 300-500 rpm and a ball milling time of 0.5-1.5 h. The temperature of the heat treatment is 800-1000°C and the insulation time is 3-5 h. The perovskite material is prepared according to the following steps: weigh the metal salt and deionized water, mix them, heat and stir until the metal salt is completely dissolved; then add ethylenediaminetetraacetic acid and citric acid to mix and stir, and adjust the pH to 7-8; the metal salt is a mixture of Sr(NO3)3 and Fe(NO3)3·9H2O; evaporate the water under heating conditions to obtain a gel-like substance, and then dry it to obtain a perovskite material precursor; place the perovskite material precursor in a muffle furnace for high-temperature heat treatment to obtain the perovskite material. The molar ratio of total metal ions, oxalic acid tetraacetic acid and citric acid in the metal salt is 1:0.9-1.1:1.8-2.2, preferably 1:1:2. Ammonia water or ammonium bicarbonate solution with a mass fraction of 20-30% is used to adjust the pH. The temperature of the drying treatment is 170-200°C and the time is 6-8h. The temperature of the high-temperature heat treatment is 900-1100°C and the insulation time is 5-8h. This further improves the product quality and improves the operating stability of the proton ceramic battery.
[0025] The present invention is further described in detail below in conjunction with specific examples, but the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. Example 1
[0026] This embodiment provides a proton ceramic battery air electrode material with low thermal expansion behavior and a preparation method thereof, as follows: (1) Weigh 10.5815 g (C2H3O2)2Sr and 20.2 g Fe(NO3)3•9H2O and mix with deionized water. Heat and stir until the metal salt is completely dissolved. Then, add 30 g ethylenediaminetetraacetic acid and 42 g citric acid monohydrate to the mixed metal salt solution in a molar ratio of citric acid monohydrate, oxalic acid tetraacetic acid and total metal ions of 2:1:1, mix and stir evenly, and adjust the pH of the mixed solution to 7-8 with 20% ammonia solution.
[0027] Under the conditions of heating (temperature is 90°C) and stirring, the water evaporates to obtain a gel-like substance. After the gel-like substance is dried at 180°C for 8 hours, a perovskite SF electrode material precursor is obtained.
[0028] Finally, the perovskite SF electrode material precursor was placed in a muffle furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, calcined for 5 hours, and naturally cooled to room temperature to prepare the perovskite SF electrode material.
[0029] (2) Weigh 1.8 g of the SF electrode material powder prepared in step (1) and 0.2 g of negative thermal expansion material ZrW2O8 (abbreviated as ZW, at this time the mass ratio of SF to ZW is 9:1, that is, the mass content of ZW is 10%), add them into a high-energy ball mill, and ball mill them at 400 rpm for 0.5 h. After taking them out, dry them, place them in a high-temperature muffle furnace and heat them to 1000°C in an air atmosphere at a rate of 5°C / min, calcine them for 5 h, and cool them naturally to room temperature to obtain a SFZW composite air electrode.
[0030] like Figure 1 (a) is the XRD refinement pattern of SFZW powder. The refinement results show that SFZW is composed of two different phases, including cubic single perovskite Sr 1-m Fe 1-x-y Zr x W y O 3-d (SP-SFZW) main phase (space group: Pm-3m, 71.3 wt%) and cubic double perovskite Sr 2-n Fe 2-a-b Zr a W b O 6-d (DP-SFZW) secondary phase (space group: Fm-3m, 28.7 wt%). Refinement parameter R wp =9.44%, R p =7.13% and χ 2 =1.48 further confirmed the reliability of the refinement.
[0031] Figure 2 This is the XRD diagram of SFZW during the heating process from room temperature to 750°C. The test results show that as the temperature increases, the SFZW composite air electrode material can always maintain its stable structure, thereby ensuring a stable phase structure in the actual working environment. This result provides strong support for the stability and reliability of the SFZW composite air electrode material. In practical applications, batteries are often affected by external environmental factors such as temperature changes, so the structural stability of the material is particularly important. The SFZW composite material maintains its structure unchanged at high temperatures, indicating that it has good thermal stability.
[0032] Comparative Example 1 This example provides a proton ceramic battery air electrode material without adding negative thermal expansion and a preparation method thereof, which is basically the same as that in Example 1, except that the negative thermal expansion material ZW is not added. The details are as follows: Weigh 10.5815g (C2H3O2)2Sr and 20.2g Fe(NO3)3•9H2O and mix with deionized water, heat and stir until the metal salt is completely dissolved; then add 30g ethylenediaminetetraacetic acid and 42g citric acid monohydrate to the mixed metal salt solution in a molar ratio of citric acid monohydrate, oxalic acid tetraacetic acid and total metal ions of 2:1:1, mix and stir evenly, and adjust the pH of the mixed solution to 7~8 with 20% mass fraction ammonia solution.
[0033] Under the conditions of heating (temperature of 90°C) and stirring, the water evaporates to obtain a gel-like substance. After the gel-like substance is dried at 180°C for 8 hours, a perovskite SF electrode material precursor is obtained.
[0034] Finally, the perovskite SF electrode material precursor was placed in a muffle furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, calcined for 5 hours, and naturally cooled to room temperature to prepare the perovskite SF electrode material.
[0035] Figure 1 (b) is the XRD refinement spectrum of the SF powder prepared in Comparative Example 1 after calcination in air for 5 hours and then naturally cooled to room temperature. The results show that SF is a pure perovskite phase.
[0036] Application Example 1 This example provides an application of the electrode material in Example 1, which is made into a symmetrical battery. The specific steps are as follows: (1) Weigh 1 g of SFZW powder prepared in Example 1, 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol, pour them into a high-energy ball mill, and mill them at 400 r / min for 30 min. Then, transfer them to the culture bottle with a dropper to obtain the required air electrode slurry; (2) Place the BZCYYb electrolyte sheet on a heating table and preheat it at 150°C. Use a spray gun to evenly spray the prepared air electrode slurry on both sides of the electrolyte under the push of nitrogen. After the liquid is completely volatilized, place the sprayed electrolyte in a high-temperature muffle furnace and calcine it at 800°C (air atmosphere) for 2 hours to obtain the required symmetrical battery. The prepared symmetrical battery was subjected to electrochemical impedance spectroscopy in the temperature range of 450~650°C. The electrochemical impedance values of the symmetrical battery with SFZW as the air electrode and BZCYYb as the electrolyte at 650°C, 600°C, 550°C, 500°C and 450°C were 0.18 Ω·cm, respectively. 2 、0.44Ω·cm 2 , 0.99 Ω·cm 2 , 2.55Ω·cm 2 、7.84Ω·cm 2 At the same time, the impedance stability of the prepared symmetrical battery was tested at 550°C for up to 300 hours under different vapor concentrations.
[0037] Application Example 2 This example provides an application of the electrode material in Example 1, which is made into a single battery. The specific steps are as follows: (1) Weigh 1 g of the air electrode powder SFZW prepared in Example 1, 10 mL of isopropanol, 2 mL of ethylene glycol, and 0.8 mL of propylene glycol, pour them into a high-energy ball mill, and ball mill at 400 r / min for 30 min. Then transfer them to the culture bottle with a dropper to obtain the required air electrode slurry.
[0038] (2) Place the prepared NiO-BZCYYb|BZCYYb double-layer sheet on a heating table and preheat it at 150°C. Use a spray gun to spray the prepared air electrode slurry evenly on the electrolyte side of the dry pressed sheet under the push of nitrogen. After the liquid is completely evaporated, place the sprayed single cell in a high-temperature muffle furnace and calcine at 800°C for 2 hours to obtain the required single cell, and test the electrochemical performance in the temperature range of 450~650°C. The peak power density of the single cell with SFZW as the air electrode in the battery mode of 650°C, 600°C, 550°C, 500°C and 450°C is 840 mW·cm -2 、597 mW·cm -2 、431mW·cm -2 、268 mW·cm -2 and 164 mW·cm -2 The electrolysis current density of the single cell with SFZW as the air electrode at 650°C, 600°C, 550°C, 500°C and 450°C was -1160 mA·cm at 1.3V, respectively.-2 、-840 mA·cm -2 、-560 mA·cm -2 、-320 mA·cm -2 and -210 mA·cm -2 .
[0039] Test result characterization and analysis 1. Phase structure stability The compatibility between the air electrode and the electrolyte is key to ensure the normal operation of PCC. Figure 3 (a) shows the XRD results of the mixture of SFZW and BZCYYb calcined at 800 °C for 2 h. The test results show that no other phases are produced except SFZW and BZCYYb, which indicates that SFZW has good chemical compatibility with BZCYYb electrolyte.
[0040] Because water is generated on the air electrode side in the PCC battery mode and introduced into the air electrode in the PCC electrolysis mode, the air electrode needs to maintain structural stability under humid air conditions. In order to test the water resistance of SFZW, the SFZW sample was treated at 550°C for 150 h under 30% H2O-Air conditions. Figure 3 (b) shows that the treated SFZW does not produce other phases except for a slight deviation in the position of the XRD main peak, which indicates that SFZW has good water resistance.
[0041] 2. Thermal Expansion Analysis In order to test the thermal expansion behavior of the material, the present application prepared dense SF (Comparative Example 1, the same below) and SFZW columnar samples, and tested the thermal expansion coefficient of the samples in the temperature range of 100~800°C using a thermal expansion instrument. Figure 4 As shown in Figure 2, the thermal expansion coefficient (TEC) of the SFZW composite material is 18.6×10 −6 K –1 , which is significantly lower than the 30.0×10 −6 K –1 SFZW composite materials with low thermal expansion coefficient reduce the internal stress caused by temperature changes and ensure the thermomechanical stability between PCC components. The low thermal expansion coefficient of SFZW composite materials is an important guarantee for the stable operation of PCC at medium and low temperatures, which helps to reduce the stress and deformation caused by temperature changes, delay material aging, and thus extend the service life of the battery.
[0042] 3. Electrochemical Impedance Analysis In order to explore the electrochemical performance of SFZW on BZCYYb proton conducting electrolyte, the present application prepared symmetrical cells of SFZW and comparative example SF calcined at 800°C, and conducted impedance tests under the condition of 5% H2O-Air. Figure 5 As shown in (a), due to the composite of negative thermal expansion materials, the impedance of SFZW is lower than that of SF. Figure 5 (b) shows that the ASR values of the SFZW symmetric cell at 650°C, 600°C, and 550°C are 0.18 Ω·cm 2 , 0.44 Ω·cm 2 , 0.99 Ω·cm 2 .
[0043] In addition, the impedance comparison test of the BZCYYb-supported symmetrical battery with SF and SFZW electrodes was carried out under 5% H2O-Air conditions at 550°C for 200 h. Compared with the symmetrical battery containing SF, the symmetrical battery containing SFZW did not show performance degradation after the test and had excellent electrochemical stability. In order to test the operating stability of the symmetrical battery with SF and SFZW electrodes under high steam concentration. In this application, the symmetrical battery with SF and SFZW electrodes was also tested in 30% H2O-Air conditions for about 100 h. The ASR results are as follows Figure 6 The impedance increase rate of SF is about 0.0078 Ω·cm 2 h -1 , while the impedance increase rate of SFZW is only 0.0019 Ω·cm 2 ·h -1 , which is much lower than the increase rate of SF. This shows that the SFZW electrode has good operating stability under high steam concentration.
[0044] Figure 7 The SEM images of the cross-sections of the SF and SFZW symmetric cells after long-term stability testing show that there is no significant difference in the porous microstructure and thickness of each layer of the two symmetric cells. It can be seen from the figure that microcracks appeared at the interface between the air electrode and the electrolyte in the symmetric cell containing SF, while the SFZW air electrode and the BZCYYb electrolyte had good contact and no cracks appeared, because the thermal matching between the air electrode and the electrolyte layer was improved.
[0045] Figure 8 (a) The thermal cycling stability of symmetric cells with SF and SFZW air electrode materials was tested at 300-600°C and 5% H2O-Air conditions. The symmetric cell was thermally cycled for 35 cycles and 100 hours at a heating rate of 30°C min-1. -1 , the cooling rate is 10°C min-1 .like Figure 8 (b) shows that the area specific impedance (ASR) of the SFZW symmetric cell increases from 0.398Ω·cm 2 Increased to 0.401Ω·cm 2 (increased by 0.7%), while the ASR value of SF increased from 0.432Ω·cm 2 Increased to 0.725Ω·cm 2 (increase of 68%), indicating that there is good thermal matching between the SFZW electrode and the electrolyte.
[0046] 4. Electrochemical performance analysis Fig. 9 (a) is the IV and IP curves of the Ni-BZCYYb|BZCYYb|SFZW single cell in fuel cell mode under H2 / air. Fig. 9 (b) IV curves of the fuel cell and electrolysis modes under 5% H2O-Air conditions. In the battery mode, the peak power densities (PPDs) of PCC at 650°C, 600°C, 550°C, and 500°C reached 840 mW·cm, respectively. -2 , 562 mW·cm -2 , 380 mW·cm -2 , and 261 mW·cm -2 The results show that the SFZW air electrode has excellent ORR activity. In the electrolysis mode, the electrolysis current density of PCC at 1.3 V at 650 °C, 600 °C, 550 °C, and 500 °C is -1160 mA·cm -2 、-840 mA·cm -2 、-560 mA·cm -2 and -320mA·cm -2 The test results show that the SFZW air electrode has excellent OER activity.
[0047] Fig.10 (a) is the SFZW single cell at 550°C and a current density of 200 mA cm -2 The PCC with SFZW air electrode operated smoothly for about 250 h in battery mode at 550 °C without obvious performance degradation. Fig.10 (b) is the SFZW single cell at 550°C and a current density of -600 mA cm -2 The single cell operated smoothly for 400 h in the electrolysis mode at 550 ° C without obvious performance degradation. This shows that SFZW is a PCC air electrode material with excellent electrochemical performance and operating temperature.
[0048] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A proton ceramic battery air electrode material with low thermal expansion behavior, characterized in that: It is made by mixing perovskite material and negative thermal expansion material in a mass ratio of 5-10:1 and heat treating. The molecular formula of the perovskite material is SrFeO 3-δ , where δ is the oxygen vacancy content; The molecular formula of the negative thermal expansion material is ZrW2O8.
2. The proton ceramic battery air electrode material with low thermal expansion behavior according to claim 1, characterized in that: The mixing is carried out using a high-energy ball mill with a rotation speed of 300-500 rpm and a ball milling time of 0.5-1.5 h.
3. The proton ceramic battery air electrode material with low thermal expansion behavior according to claim 1 or 2, characterized in that: The heat treatment temperature is 800-1000°C and the insulation time is 3-5h.
4. The proton ceramic battery air electrode material with low thermal expansion behavior according to claim 1, characterized in that: The perovskite material is prepared according to the following steps: Weigh a metal salt and deionized water, mix them, heat and stir until the metal salt is completely dissolved; then add ethylenediaminetetraacetic acid and citric acid, mix and stir, and adjust the pH to 7 to 8; the metal salt is a mixture of Sr(NO3)3 and Fe(NO3)3·9H2O; The water is evaporated under heating conditions to obtain a gel-like substance, which is then dried to obtain a perovskite material precursor; The perovskite material precursor is placed in a muffle furnace for high-temperature heat treatment to obtain the perovskite material.
5. The proton ceramic battery air electrode material with low thermal expansion behavior according to claim 4, characterized in that: The molar ratio of total metal ions, oxalic acid tetraacetic acid and citric acid in the metal salt is 1:0.9~1.1:1.8~2.2, preferably 1:1:
2.
6. The proton ceramic battery air electrode material with low thermal expansion behavior according to claim 4, characterized in that: Use 20-30% ammonia water or ammonium bicarbonate solution to adjust the pH.
7. The proton ceramic battery air electrode material with low thermal expansion behavior according to claim 4, characterized in that: The drying process is carried out at a temperature of 170 to 200°C and a time of 6 to 8 hours.
8. The proton ceramic battery air electrode material with low thermal expansion behavior according to any one of claims 4 to 7, characterized in that: The temperature of the high temperature heat treatment is 900-1100°C and the insulation time is 5-8h.